Character Education Program Management to Improve Student's Religious Attitudes in Madrasah Aliyah - Hamidatul Ula; Suwarno Suwarno (Program Studi Manajemen Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2023)
This study aims to describe the management of character education programs to improve students' religious attitudes in the era of information disruption. The research method used is a qualitative research method with a phenomenological approach. Data collection techniques were carried out by interview, observation, documentation, and triangulation. The data analysis technique was carried out in several stages: data collection, condensation, data display, and conclusion. This study found that managing character education programs to improve students' religious attitudes was carried out through several stages. The first stage was planning which was documented in the madrasa curriculum document, madrasa work plan document, and madrasa context analysis document. The second stage is organizing, namely by forming a division of tasks and religious teams, providing facilities both in the form of facilities and non-facilities. The third stage is implementation through various program activities in the form of extracurricular activities, routine activities, and extracurricular activities. And the fourth stage is the supervision carried out by the religious team in coordination with subject teachers, homeroom teachers, and counseling guidance, as well as establishing communication with students' parents.